Denshawai and Cromer in the poetry of Ahmad Shawqi - Al-Rifai, Nada Yousuf (Advances in Social Sciences Research Journal, 2020)
Abstract In the summer of 1906, a group of British Army officers went on a pigeon hunt near the Nile Delta town of Dinshaway. It came as no surprise then, that during the pigeon hunt, an errant gunshot set fire to the village’s wheat supply. Enraged as they watched their precious grain go up in smoke, villagers tried to seize the offending gun and a riot broke out during which several people were hurt and two of the British officers were wounded. As they tried to escape, one officer died from heatstroke. The British response was brutal. Returning in force to the village, a military tribunal convicted 52 of the villagers of pre-meditated murder; though most were just beaten, four were hanged. On April 1, 1907, less than a year after the Denshawai issue, Lord Cromer resigned as governor of Egypt since 1883, and left Egypt. His departure allowed the anger among the patriots, who were critical of him, to be set free, primarily because of his offense to Islam, and because he did not make any sincere effort to try to understand the aspirations of Egyptians. Ahmad Shawqi’s "Farewell to Lord Cromer," was composed on the occasion of the latter’s departure from Egypt. After his resignation, Lord Cromer gave a farewell speech at the Khedival Opera House in Cairo on May 4, 1907. Cromer’s speech provoked a chorus of protest by the nationalists as well as by forces allied with the Khedive whom Shawqi was one of.